Therapeutic target biomarkers of patient-derived xenograft models of gastric-type cervical adenocarcinoma - Yuki Kojima; Hiroshi Yoshida; Toshihiro Okuya; Hitomi S Okuma; Tadaaki Nishikawa; Maki Tanioka; Kazuki Sudo; Emi Noguchi; Tatsunori Shimoi; Kenji Tamura; Yasuhito Tanase; Masaya Uno; et al. (Gynecologic Oncology Reports, 2023)
Background: Most cervical adenocarcinomas are associated with human papillomavirus (HPV). Gastric-type cervical adenocarcinoma (GAS), an HPV-independent adenocarcinoma, shows an aggressive clinical feature, resulting in a poor prognosis. Resistance to chemotherapy poses a difficulty in managing patients with metastatic GAS. We aimed to establish patient-derived xenografts (PDXs) of tumors from two patients with GAS and evaluated protein biomarkers for drug development using immunohistochemistry. Methods: Two PDXs were established 78 and 48 days after transplanting the patient’s tumor tissues into immunodeficient mice, respectively. PDX and patient’s tumor samples were stained for HER2, HER3, PMS2, MSH6, PanTrk, and ARID1A to evaluate biomarkers for therapeutic targets. In addition, whole exome sequencing and RNA sequencing were performed on available samples. Results: The pathological findings in morphological features and immunohistochemical profiles from the established PDXs were similar to those from the patients’ surgical tumor specimens. HER3 was overexpressed in the patient’s tumors, and the corresponding PDX tumors and HER2 was weakly stained in both types of tumor samples. In all PDX and patient tumor samples, PMS2, MSH6, and ARID1A were retained, and PanTrk was not expressed. In addition, a total of 10 samples, including tumor tissue samples from 8 other GAS patients, were evaluated for HER3 expression scores, all of which were 2 + or higher. Conclusions: In summary, we evaluated biomarkers for therapeutic targets using newly established PDX models of GAS. Frequent HER3 overexpression and HER2 expression in GAS tumors suggest the possibility of new treatments for patients with GAS by targeting HER3 and HER2.